Limited Distal Arch Open Stenting for Type B Aortic Dissection with an Enlarged Ulcer-Like Projection, Complicated by Abdominal Aortic Occlusion - Hata, Mitsumasa; Akiyama, Kenji; Orime, Yukihiko (The Thoracic and Cardiovascular Surgeon Reports, 2016)
A 79-year-old man underwent bifurcated graft replacement for abdominal aortic aneurysm, but the graft was totally occluded owing to an acute type B aortic dissection. We could not have access to the root for performing endovascular stenting for dissecting aneurysm. Furthermore, it was difficult to remove the aneurysm via a left thoracotomy because it was impossible to perfuse the lower body with blood from the femoral artery and also a left axillary arterial cannulation was unusable. Herein, we report a patient who was successfully treated with open surgical aortic stenting for an enlarged ulcer-like projection complicated by a type B aortic dissection.
Keywords: aortic aneurysm; cardiovascular surgery; aortic stent